The triumph of the Bolshevik Revolution - Elizondo Calderón, William (2018)
On the occasion of 100 years of the bolshevik revolution, this article is a brief presentation on the meaning, repercussions, immediate antecedents and bolshevik strategy for the seizure of power in October 1917. The choice of the opportune moment for the armed insurrection and the issuance of the first bolshevik decrees responded to the most pressing needs of the population. This enabled popular support to take and consolidate power. They overthrew the power of the bourgeoisie and established a government of workers and peasants, attracting world attention as an alternative model to capitalist development in order to end social inequalities. The construction of soviet socialism takes place in the context of enormous difficulties, in an extensive territory and with very diverse productive forms, in addition to the conflict with the old ruling classes that sought the restoration of capitalism or the tsarist autocracy.